2014
DOI: 10.1590/s1516-35982014000300002
|View full text |Cite
|
Sign up to set email alerts
|

Corn plant arrangement and its effect on silage quality

Abstract: -This experiment was carried out to evaluate the effects of the row spacing between corn plants on silage quality. Different spacing between corn rows (40, 60, and 80 cm) was used, but the population of plants was maintained around 65,000/ha in all treatments. Analysis of variance was carried out and means were compared by Tukey's test at 5% of probability. A reduction in row spacing provided better spatial distribution of plants, but did not alter morphological composition or dry matter production. The corn w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
(26 reference statements)
3
3
1
Order By: Relevance
“…Despite the significant differences between some of the morphological characteristics of corn -percentages of stalks + sheaths + panicles, leaves, and bracts -in the present study (Table 2), these only differed slightly between the cropping systems, which shows the viability of intercropped crops in tropical regions. The values found in the present study are similar to those reported by several authors Skonieski et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…Despite the significant differences between some of the morphological characteristics of corn -percentages of stalks + sheaths + panicles, leaves, and bracts -in the present study (Table 2), these only differed slightly between the cropping systems, which shows the viability of intercropped crops in tropical regions. The values found in the present study are similar to those reported by several authors Skonieski et al, 2014).…”
Section: Resultssupporting
confidence: 93%
“…Ether extract content varied from 0.83 to 4.88% of the DM; these values are consistent with reports for corn silage in Brazil (CQBAL, 2014;Skonieski et al, 2014). The high variability can be explained by the different commercial hybrids used in different farms, the harvesting time, and potential microbial degradation in air-exposed silage.…”
Section: Chemical Compositionsupporting
confidence: 88%
“…The mean TDN (65.2 ± 3.6%) was lower than that reported by Tine et al (2001;69.5%) and Skonieski et al (2014;68.3%), most likely due to the lower lignin content reported by those authors for corn silage (1.5 and 2.9% of the DM, respectively). Lignin has a negative effect on calculated TDN values (Weiss et al, 1992) when ADL is used to calculate truly digestible fiber.…”
Section: Chemical Compositioncontrasting
confidence: 57%
“…Regarding forage quality, the narrow row production system neither had any impact on the nutritive value of maize, such as DMD, ADF, NDF and CP (Widdicombe & Thelen 2002), nor on the concentration of starch, simple sugars and digestibility of NDF (Beres et al 2008). However, Baron et al (2006) and Skonieski et al (2014) recorded higher content of CP for conventional rows compared with the narrow rows.…”
Section: Original Papermentioning
confidence: 83%
“…Also Cox and Cherney (2001) found significantly lower CP concentrations at 116,000 plants/ha (52 g/kg) compared with 80,000 plants/ha (55 g/kg). Regarding row spacing, Skonieski et al (2014) recorded a significantly higher content of CP (70 and 68 g/kg) for conventional rows (0.60 and 0.80 m) compared with narrow rows (54 g/kg at 0.40 m). Also, Baron et al (2006) found marginally higher protein concentration (74 g/kg) in comparison with narrow rows (72 g/kg).…”
Section: Forage Qualitymentioning
confidence: 93%